N-FORMYL-MET-LEU-PHE-INDUCED OXIDATIVE BURST IN DMSO-DIFFERENTIATED HL-60 CELLS REQUIRES ACTIVE HSP90, BUT NOT INTACT MICROTUBULES - Vrba, Jiří; Modrianský, Martin (Biomedical papers, 2004)
In this study we examined whether microtubules and heat shock protein 90 (Hsp90) are involved in phorbol myristate acetate (PMA) and N-formyl-Met-Leu-Phe (fMLP)-induced oxidative burst in DMSO-differentiated HL-60 cells. Our results showed that microtubule interfering agents, paclitaxel (1-5 µM), colchicine (1-100 µM), nocodazole (1-20 µM), and vincristine (1-50 µM), did not affect either PMA or fMLP-induced oxidative burst. In contrast, radicicol, an inhibitor of Hsp90, inhibited fMLP-induced oxidative burst in time and concentration-dependent manner where IC50 value for 30 min pre-incubation was 16.5 ± 3.5 µM radicicol. We conclude that both PMA and fMLP-induced oxidative burst in DMSO-differentiated HL-60 cells is microtubule-independent while the latter requires Hsp90 activity.
Keywords: Radicicol/Hsp90/Microtubules/Oxidative burst/HL-60